Estudo longitudinal do perfil salivar proteico de crianças nos primeiros meses de vida - Damasceno, Juliana Ximenes (2015)
Studies on the development of salivary composition in the first year of life can promote the information about the immune maturation in children. Saliva is the most easily available and accessible body fluid, which makes it one of the most sought after tools in diagnostic and biomarks. In this context, this thesis, constituted by 01 article aimed to characterize salivary proteins in the first months of life using unidimensional electrophoresis. On this study, stimulated whole saliva was obtained from 79 babies, both genders at first and third months of life. Supernatants were analyzed, salivary flow rate (mL/min) was calculated for each child and total protein concentration determined by the Bicinchoninic Acid Protein (BCA) method. Proteins were characterized according to their molecular weights within the unidimensional electrophoresis. The results showed salivary flow rates significantly different (p = 0.000) between the first and third months of life, being the flow rate of whole saliva at third month (Median: 0.10, min-max: 0.02-0.2 mL/ min) higher than at first month (Median: 0.02, min-max: 0.02-0.06mL/min). The weight in Kg showed significant differences (p = 0.000) between the first month (Median: 3.32, Min-Max: 2.02-4.03) and third months (Median: 6.26, Min-Max: 4.49-9.30).This study also showed difference concerning to total protein concentration between saliva of the first and third months (p = 0.000), being higher concentrations found in first (Median: 1.293, min-max: 0.427-3.931 μg/mL) than in third (Median: 0.720, min-max: 0.164-2.244 μg/mL). Bands with 150 (p=0.004), 100 (p=0.000), 42 (p=0.001), 30 (p=0.039), 25 (p=0.001), 20 (p=0.009), 15 (p=0.011) and 13 kDa (p=0.002) presented higher intensity in whole saliva of the first month. A band with 218 kDa was expressed exclusively during the third month of life. Apgar at 1 min was positively correlated with the total number of bands expressed in the first (p = 0.019) and third months (p = 0.014). In conclusion, the concentration of total salivary proteins decreases between the first and third months, and the expression of the salivary proteins changes depending on the age, where the expression of specific protein bands is specific to certain developmental stages during the first 3 months.